Metody obliczania niezborności indukowanej chirurgicznie - Wilczyńska, Olena; Wilczyński, Michał (Klinika Oczna / Acta Ophthalmologica Polonica, 2009)
Evaluation of surgically induced astigmatism is important, as it allows to thoroughly assess the influence of surgical incision on corneal refraction. This influence can be established by calculating surgically induced astigmatism according to an appropriate mathematical method. The purpose of the study was to describe various mathematical methods used in the current literature to calculate surgically induced astigmatism. When comparing results of calculation of surgically induced astigmatism among different studies, it is necessary to take into account values obtained with the use of the same method of calculation, as various methods evaluate astigmatism differently.